Distinct cell type–specific mechanisms underlie cognitive dysfunction during persistent integrated stress response activation - Kristof Torkenczy; Lucas C. Reineke; Sean W. Dooling; Benjamin W. Henderson; Benjamin Yang; Dongze He; Richard M. Myers; Peter Walter; Stefka Tyanova; Mauro Costa-Mattioli (Proceedings of the National Academy of Sciences, 2026)
Persistent activation of the integrated stress response (ISR) is a central driver of cognitive decline in both neurodevelopmental and neurodegenerative disorders. However, the cell type–specific mechanisms underlying these deficits remain poorly understood. By integrating single-cell RNA-seq and single-cell assay for transposase-accessible chromatin sequencing, we generated a brain ISR atlas using Ppp1r15b R658C mice, a clinically relevant model of intellectual disability characterized by selective and persistent ISR activation. We find that distinct brain cell types differentially engage transcriptional and chromatin remodeling programs. Notably, selective deletion of the major ISR downstream effector ATF4 in GABAergic neurons, but not in glutamatergic neurons, exacerbates ISR-mediated cognitive decline in Ppp1r15b R658C mice, demonstrating that different neuronal subtypes rely on distinct ISR effectors. We define a molecular single-cell signature of persistent ISR activation that serves as a metric of ISR-mediated cellular vulnerability and as a biomarker for cognitive dysfunction across human cognitive disorders. These findings demonstrate that cell type–specific responses drive cognitive dysfunction during persistent ISR activation.